Brief Review on Formation Control of Swarm Robot - Ade Silvia Handayani; Siti Nurmaini; Iryadi Yani (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
This paper presented review formation control ofswarm robot. Recently the problems formation control of swarmrobots has attracted much attention, and several formationcontrol schemes were proposed based on various strategies. Theformation control strategies to solved these problem on swarmrobots, with considering regulation concept in control theory.Swarm intelligence algorithms takes the full of advantages of thefeature of swarm robotics, and provides a great solution forproblem formation control on swarm robots.